The Concept of Mahabbah and Makrifah in the Sufism Thought of Rabiah al-Adawiyah and al-Ghazali: Relevance for Contemporary Islamic Spirituality - Kaharu, Ninin Riska Syahfitri; Santalia, Indo (IJoIS: Indonesian Journal of Islamic Studies, 2024)
This study analyzes the thought of Sufism Rabiah al-Adawiyah and al-Ghazali, two central figures in the Islamic spiritual tradition. Rabiah al-Adawiyah developed the concept of mahabbah (love), which is sincere and deep love for Allah as a form of pure selfless devotion. Al-Ghazali, on the other hand, introduced the concept of makrifah (knowing), which leads to a spiritual understanding of God through deep inner experience. This study uses the literature study method, by utilizing relevant literature, to examine these concepts in the context of the development of Sufism. The results of the research are expected to provide insight into the influence of these two figures' thoughts on Islamic spirituality and its application in the lives of Muslims today.